Adventures and misfortunes of "écriture féminine" - Segarra, Marta (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Écriture féminine, as it was defined in the 1970s within French theoretical feminism, does not correspond to literature written by women (referred to by many critics of the past as littérature féminine), nor does it presuppose that women write in a similar style or on similar issues. This paper examines the misunderstandings that have arisen around écriture féminine, both in France and in the United States, where the term “French Feminism” was coined to label certain France-based theorists, albeit from different backgrounds, notably Hélène Cixous, Luce Irigaray and Julia Kristeva. The three of them were often considered essentialists or differentialists, although their texts do not favor this interpretation. The tensions that arose within the French Women’s Liberation Movement (MLF) contributed to fuel the polemic. The opposition between differentialism and universalism has led, almost half a century later, to other debates that mark contemporary theoretical feminisms in France.